Inhibition of IL11 Signaling Reduces Aortic Pathology in Murine Marfan Syndrome. Issue 5 (9th February 2022) - Lim, Wei-Wen; Dong, Jinrui; Ng, Benjamin; Widjaja, Anissa A.; Xie, Chen; Su, Liping; Kwek, Xiu-Yi; Tee, Nicole G.Z.; Jian Pua, Chee; Schafer, Sebastian; Viswanathan, Sivakumar; Cook, Stuart A.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Marfan syndrome (MFS) is associated with TGF (transforming growth factor) β–stimulated ERK (extracellular signal-regulated kinase) activity in vascular smooth muscle cells (VSMCs), which adopt a mixed synthetic/contractile phenotype. In VSMCs, TGFβ induces IL (interleukin) 11) that stimulates ERK-dependent secretion of collagens and MMPs (matrix metalloproteinases). Here, we examined the role of IL11 in the MFS aorta. Methods: We used echocardiography, histology, immunostaining, and biochemical methods to study aortic anatomy, physiology, and molecular endophenotypes in Fbn1 C1041G/+ mice, an established murine model of MFS (mMFS). mMFS mice were crossed to an IL11-tagged EGFP (enhanced green fluorescent protein; Il11 EGFP/+ ) reporter strain or to a strain deleted for the IL11 receptor ( Il11ra1 −/− ). In therapeutic studies, mMFS were administered an X209 (neutralizing antibody against IL11RA [IL11 receptor subunit alpha]) or IgG for 20 weeks and imaged longitudinally. Results: IL11 mRNA and protein were elevated in the aortas of mMFS mice, as compared to controls. mMFS mice crossed to Il11 EGFP/+ mice had increased IL11 expression in VSMCs, notably in the aortic root and ascending aorta. As compared to the mMFS parental strain, double mutant mMFS: Il11ra1 −/ − mice had reduced aortic dilatation and exhibited lesser fibrosis, inflammation, elastin breaks, and VSMC loss, which was associated with reduced aortic COL1A1 (collagen type I alpha 1 chain), IL11, MMP2/9, and phospho-ERK expression. To explore therapeutic targeting of IL11 signaling in MFS, we administered either a neutralizing antibody against IL11RA (X209) or an IgG control. After 20 weeks of antibody administration, as compared to IgG, mMFS mice receiving X209 had reduced thoracic and abdominal aortic dilation as well as lesser fibrosis, inflammation, elastin breaks, and VSMC loss. By immunoblotting, X209 was shown to reduce aortic COL1A1, IL11, MMP2/9, and phospho-ERK expression. Conclusions: In MFS, IL11 is upregulated in aortic VSMCs to cause ERK-related thoracic aortic dilatation, inflammation, and fibrosis. Therapeutic inhibition of IL11, imminent in clinical trials, might be considered as a new approach in MFS.